Volatile and sensory profiling of Shiraz wine in response to alcohol management: comparison of harvest timing versus technological approaches. (July 2018) - Longo, Rocco; Blackman, John W.; Antalick, Guillaume; Torley, Peter J.; Rogiers, Suzy Y.; Schmidtke, Leigh M.
Abstract: The aim of this study was to compare the volatile and sensory profiles of Australian Shiraz red wines produced by several methods to achieve alcohol concentrations of 10.5 and 13.5% v/v. These levels were considerably lower contents than the commercial wine (16-17% v/v) that was produced from this vineyard site. Wines were produced by: (i) harvest timing (19.3, 24 and 29.3 Brix); (ii) blending equal proportions of early harvest (19.3 Brix) and late harvest wines (29.3 Brix); and (iii) dealcoholization using reverse osmosis followed by a membrane contactor. Dealcoholization caused a significant loss of volatile compounds, particularly esters, while the blending treatment had an averaging effect on most analytes. Sensory descriptive analysis of treatments with 10.5% v/v alcohol showed that the perception of the herbaceous attribute was more intense in the early harvest wines in comparison to the dealcoholized wines, while those of dark fruit, raisin/prune, astringency and alcohol were lower. No sensory differences were found amongst the 13.5% v/v wines, except for alcohol . Sensory and compositional data were modelled by means of Common Dimension (ComDim) multi-block analysis and indicated which chemical components are important to the perceived wine sensory properties. Insights from this study will provide knowledge that may be applied to control or moderate both unripe sensory attributes in addition to a deficiency of ripe fruit aromas or mouthfeel characteristics in reduced-alcohol red wines. Graphical abstract: Highlights: Sensory profile of reduced alcohol wines may depend on the alcohol reduction method. Minimal sensory changes only were perceived in the dealcoholized wines. Blended wines exhibited most of the sensory attributes of the late harvest component. Blending could be a commercial solution to manage wine alcohol content.